Soil organic carbon dynamics in sugarcane crop in south-central Brazil - Olaya, Adriana Marcela Silva (2014)
Sugarcane cropping is an important component of the Brazil´s economy. As the main feedstock used to produce ethanol, the area occupied with this crop has meaningfully increased in the last years and continues to expand in order to attend to the national and international demand of this biofuel. Despite that it has been demonstrated that land-use transition into sugarcane can negatively impact the soil carbon (C) dynamics, little is known about the effect of those land use changes (LUC) processes on the distribution of soil organic carbon (SOC) within particle-size classes, and how management practices in sugarcane can contribute to the C restoration. In this sense the main objective of this study was to evaluate through a modelling application the SOC dynamics in the sugarcane crop in response to LUC and different management scenarios. For a better understanding of LUC impact on C content in both particulate organic matter and mineral-associated fraction, we performed physical soil C fractionation in 34 study areas involving the three major land-use systems affected by sugarcane expansion. Also, biometric measurements were executed in sugarcane plant and ratoon crop in order to use those data in the model parameterization as well as to recalculate the payback time of the C debt through C conversion ratio reported in the literature. Finally, we parameterized and validate the CENTURY ecosystem model for sugarcane, pastures and annual cropland by using a data-set previously collected by the Laboratório de Biogeoquímica Ambiental (CENA-USP); then different scenarios of sugarcane management were simulated: i) SC1 - Green harvesting; ii) SC2 - Green harvesting plus organic amendments and iii) Green harvesting + low N inputs. Our results showed that the C content depletion for conversion from native vegetation and pastures to sugarcane is caused by C losses in the labile fraction (37%) as wells as in the stabilized pool associated to the mineral fraction (30%). Above and belowground biomass quantification indicated a total sugarcane carbon inputs ranging from 29.6 Mg C ha-1 to 30.6 Mg C ha-1. Considering a C retention rate of 13% we estimated net carbon changes of 0.58 to 0.6 Mg C ha-1 year-1, which contribute to reduce the payback times for sugarcane biofuel carbon debts in 3.3 and 1.2 years for Cerrado wooded and pasture conversions into sugarcane respectively. The modelling study supported the Century model as a tool to access the SOC dynamics following land-use conversion and different soil management in in sugarcane. Long-term simulations suggested that changes in the sugarcane harvest from burning to green harvesting increase the soil C stock in an average of 0.21 Mg ha-1 year-1; however the potential of C accumulation is still higher when organic amendments as vinasse and filter cake are add to the soil, with mean values varying between 0.34 and 0.37 Mg ha-1 year-1 in SC2 and SC1 respectively. By analyzing the SOC dynamic at each scenario simulated, we estimated a time span of 17 and 24 years for soil C restoration in clay and sandy soils under pastures with priority suitability (SC3). The number of years was projected to be higher in clay soils with regular suitability (40 years).